Penerapan Model Pembelajaran Cooperative Learning Two Stay Two Stray untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII.A MTsN 1 Bengkalis - Iriyany, Firda (STAIN Bengkalis, 2021)
Mathematics learning outcomes of class VIII.A students of MTsN 1 Bengkalis are still relatively low and have not reached the minimum completeness for each basic competencies. This is because there are still many students who are not active yet in learning activities and their assumption about mathematics is a difficult subject to understand. This research is a Classroom Action Research conducted in 2 cycles with 6 meetings using the cooperative learning model type two stay two stray with 35 students as research subjects. Data collected by observation technique and tests before the action and in each cycle. The findings of this study were there is an increase in the completeness of mathematics learning outcomes by 31.43% from 28.57% before the action to 60% after the second cycle. The results showed that the cooperative learning model type two stay two stray can improve mathematics learning outcomes.Hasil belajar Matematika siswa kelas VIII.A MTsN 1 Bengkalis masih tergolong rendah dan belum mencapai ketuntasan minimal untuk setiap kompetensi dasar. Hal ini disebabkan karena masih banyak siswa yang kurang aktif dalam kegiatan pembelajaran serta asumsi siswa yang menganggap pelajaran Matematika adalah pelajaran yang susah dimengerti. Penelitian ini merupakan Penelitian Tindakan Kelas yang terdiri dari 2 siklus dengan 6 pertemuan menggunakan model pembelajaran cooperative learning tipe two stay two stray dengan subjek penelitian berjumlah 35 siswa. Teknik pengumpulan data yang digunakan adalah observasi dan tes sebelum tindakan dan pada masing-masing siklus. Temuan penelitian ini adalah terjadi peningkatan ketuntasan hasil belajar matematika sebesar 31.43% dari 28,57% sebelum tindakan menjadi 60% setelah siklus II. Hasil penelitian menunjukkan bahwa model pembelajaran cooperative learning tipe two stay two stray dapat meningkatkan hasil belajar matematika.